Differential cross sections for elastic and inelastic positronium-hydrogen-atom scattering - Adhikari, S. K. [UNESP] (American Physical Soc, 2001)
A time reversal symmetric regularized electron exchange model was used to elastic scattering, target elastic Ps excitations and target inelastic excitation of hydrogen in a five state coupled model. A singlet Ps-H-S-wave resonance at 4.01 eV of width 0.15 eV and a P-wave resonance at 5.08 eV of width 0.004 eV were obtained using this model. The effect on the convergence of the coupled-channel scheme due to the inclusion of the excited Ps and H states was also analyzed.
Keywords: Binding energy; Electromagnetic wave propagation; Electron energy levels; Electron scattering; Electron transitions; Hydrogen; Mathematical models; Partial differential equations; Phase shift; Positrons; Resonance; Hydrogen atom scattering; Positronium; Atomic physics